식료품 제조업에서 CSR 활동과 경영 효율성 분석 - 강다연; Kang Da-yeon; 이기세; Lee Ki-se (농촌경제, 2025)
최근 인구구조의 변화는 소비 패턴의 변화도 가져왔다. 본 연구에서는 현시점에서 식료품 제조업의 기업들이 효율적인 경영활동을 잘하고 있는지를 분석하였으며, 이러한 기업의 경영 효율성과 사회책임 활동과는 어떠한 관련성이 있는지를 검증하였다. 이를 위해 2022년 상장된 식료품 기업을 대상으로 분석하였다. 분석 방법으로는 각 기업의 경영 효율성을 측정하기 위해 DEA를 이용하였고, 기업의 CSR 활동과 경영 효율성과의 관련성을 검증하기 위해서는 상관분석, 차이 분석, 회귀분석을 이용하였다. 연구 결과 BCC 모형에서 효율적인 기업으로는 총 25개 기업, CCR 모형에서는 16개 기업이 효율적인 경영활동을 하는 것으로 확인되었다. 규모의 효율성에서는 효율적인 운영기업이 19개로 나타났으며, 규모의 수익성에서는 규모의 불변이 19개 기업, 규모의 체증이 5개 기업, 규모 체감이 7개 기업으로 확인되었다. 그리고 기업의 CSR 활동 여부와 경영 효율성과의 관련성은 유의하지 않는 것으로 나타났다. 하지만 CSR 활동 점수가 높을수록 기업의 BCC가 제고됨을 확인하였다. Recent changes in population structure have also brought about changes in consumption patterns. This aims to study analyse whether food manufacturing companies conduct efficient management activities and examine the relationship between management efficiency and social responsibility activities. For this purpose, DEA was employed, and its results were tested using correlation, difference, and regression analyses, to explore the relationship between corporate social responsibility (CSR) and management efficiency. A total of 25 efficient companies were identified under the BCC model and 16 under the CCR model. Regarding scale efficiency, 19 companies were efficient in terms of scale profitability, 19 under scale constancy, 5 under scale increase, and 7 under scale decrease. Additionally, the relationship between corporate CSR activities and management efficiency was not statistically significant. However, results confirmed that higher CSR activity score were associated with higher BCC.